The Impact of Foreign Exchange Rate Risk on China’s Commercial Banks - Zhang, Zhu (2009)
Abstract China is growing integration into the global economy and the fact that any change in its currency exchange rate will have a enormous impact internally as well as externally. The issues of the RMB appreciation and the optimal choice for China's exchange rate regime have become of utmost concern to China and many other countries. (Yi, 2007) From 1994 to 2005, China has been adopting the fixed rate system as its exchange rate system which was at market rate, namely the single exchange rate regime. However, a new exchange rate system (the dual exchange rate regime) has been implemented since July 2005，which can be used to manage floating exchange rate in the dynamic marketplace. In reality, China's commercial banks did not pay close attention to exchange rate risk in the past few years, so that the awareness of risk management is not strong high in banking. This research is based on China RMB reform of exchange rate. The main objective of this paper is to present both theoretical and empirical analyses of the impact of exchange rate risks on China's commercial banks. The paper is composed of four parts. The first chapter starts with an overview of China's exchange rate policy and economic development. The objectives, methodology and data collection will also be presented in this chapter. In the second part will be the literature review, the definition of the exchange rate, exchange rate risk, and the economic theory of exchange rate are mainly put forward to support the following case study. Chapter three, which constitutes the main body of this paper, sets up an empirical case study that describes how exchange rate affects China's commercial banks. The final chapter contributes to the rapidly growing literature by exploring a desire exchange rate regime of China in the light of latest theoretical views and empirical methods. At the same time, it is suggested the further measure can be taken to manage exchange rate risk in China's commercial banks.